Analysis of the Management of Village Fund Allocation in the Health Program in Tuntungan II Village, Deli Serdang Regency - Sari, Anggi Novita; Dahlan, Ulfiyah Az-Zahra; Ainy K., Nabilla Tawaqal; Ritonga, Putri Alvia; Hasibuan, Indah Doanita (PROMOTOR, 2024)
One of the problems of health development that occurs in the villages of Deli Serdang Regency is the high level of community diversity, which results in the complexity of the problems that arise. To complete development, especially in Tuntungan II Village, larsger funds are needed. Based on the information above, the researcher is interested in conducting further research on "Analysis of the Management of Village Fund Allocation (ADD) on Health Programs in Tuntungan II Village", which was conducted using qualitative research methods. The aspect analyzed was the allocation of village fund management on welfare programs. The results show that the two main sources of village income are the Village Development Movement program funds from the APBD of Deli Serdang Regency and village funds provided starting in 2021 from the APBN. The village fund policy process in Tuntungan II Village is strongly influenced by the development planning meeting (Musrenbang), the result of which is the RAPBDes document. The increase in village funds each year shows the government's commitment to development, as outlined in the third Nawacita. Village development is influenced by the village head, village officials, political factors, and kinship; without professionalism, the process can be hampered. Using village budgets for health development becomes more difficult as there are limitations in basic management of health workers.